PATH-33. HEXOKINASE 2 KNOCKOUT VIA CRISPR REDUCES DOWNSTREAM GENE EXPRESSION, IMPLICATING A REDUCTION IN CELL PROLIFERATION AND DRUG RESISTANCE. (5th November 2018) - Blakeway, Daniel; Karakoula, Katherine; Morris, Mark; Rowther, Farjana; Ashton, Kate; Dawson, Tim; Darling, John; Warr, Tracy
Abstract: HK2 has a prominent role in aerobic glycolysis and has been implicated in many cancer types including GBM, with overexpression associated with drug resistant phenotypes. Previously, we have demonstrated HK2 expression was upregulated between 6 to >1000 fold in GBM biopsy tissue (n=100) and patient derived cell cultures (n=13), compared to normal brain tissue. In the present study we have knocked out HK2 using CRISPR in patient-derived cultures (n=3) and the established cell line U251MG, to determine changes in the rate of cell proliferation and drug sensitivity. Additionally downstream expression changes were investigated via Qiagen profiler arrays, across 84 key genes involved in the regulation and enzymatic pathways of glucose metabolism. A substantial growth rate reduction between 38 to 44% (p<0.007) was demonstrated in CRISPR-modified cultures after 7 days compared to non-CRISPR cultures. Sensitivity to metformin was also significantly (p<0.0001) increased in response to HK2 knockout, where average ID50 values were 60% lower in cultures. Additionally CRISPR modified cultures yielded greater synergistic (CI<1) and additive effects (CI=1), with metformin and temozolomide combination treatment. Array data revealed an extensive change in downstream gene expression in CRISPR-modified cultures, between 25 to 48 genes were downregulated compared to the corresponding non-CRISPR cultures. Furthermore CRISPR-modified cultures demonstrated a similar reduction in downstream expression when compared to GBM biopsy tissue, conversely a greater number of genes had unchanged expression levels compared to normal brain tissue. This study demonstrates the predominant role of HK2 within the glycolytic pathway, with overexpression potentially key in driving the genetic alterations downstream. HK2 knockout revealed considerable ubiquitous reductions in downstream gene expression compared to GBM biopsy tissue and non-CRISPR cultures. Additionally an increase in drug sensitivity was depicted with the loss of HK2 signifying the potential of HK2 inhibition as a novel therapy in a significant subset of GBM.